FRI0534 PATIENT-REPORTED MEASURES OF DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS VARY ACROSS THE NORDIC COUNTRIES, RESULTS FROM A NORDIC COLLABORATION. (2nd June 2020) - Delcoigne, B.; Aarrestad Provan, S.; Hammer, H. B.; DI Giuseppe, D.; Frisell, T.; Glintborg, B.; Gröndal, G.; Gudbjornsson, B.; Hetland, M. L.; Michelsen, B.; Nordström, D.; Relas, H.; et al.
Abstract : Background: Disease activity in rheumatoid arthritis (RA) patients is measured through composite scores which are considered treatment targets and thus facilitate clinical decision making. Scores often combine a mix of objective and subjective measures, and, although the latter (e.g. pain, patient's global, 28 tender joint count (TJC)) may be impacted by contextual and cultural factors, these clinical metrics are often assumed to be comparable across different settings and reflecting the RA disease. Objectives: To explore whether there are systematic differences in patient-reported measures of RA disease activity (i.e. TJC and a measure of pain on a Visual Analog Scale (VAS)) across countries, at similar time-points in the course of the RA disease, taking objective measures of concomitant disease activity and other factors into account. Methods: RA patients starting a first ever tumor necrosis factor inhibitor (TNFi) 2008 through 2017 were identified in rheumatologic registers in five Nordic countries. Data were pooled for analysis. Clinical metrics were retrieved at three time-points: at TNFi start, and after three and twelve months, irrespective of treatment. Baseline clinical variables distributions were compared between countries. The correlation between pain and patient's global VAS was calculated with the Pearson correlation coefficient (r). At each time-point the subjective measures (TJC and pain) were compared between countries and analyzed with linear models: (i) crude; (ii) adjusted for age, sex, birth decade, disease duration (DD), year of TNFi treatment start (year), C-reactive protein (CRP) and 28 swollen joint count (SJC)) from the time-point in question. Results: A total of 23 796 RA patients were included (Table 1 ). At baseline, the significant differences between Nordic countries for TJC and pain (crude model) were slightly modified after adjustment but remained statistically significant (Table 2 ). Compared to baseline, the inter-countries differences were reduced at 3 and 12 months, but also were statistically significant (Figure 1 ). Conclusion: In this observational study of 23 796 RA patients from 5 Nordic countries starting 1 st TNFi, patient-reported variables related to RA disease activity (pain VAS, TJC) varied across countries. These differences were not explained by differences in demographic (age, sex, birth decade, year) or objective RA measures (DD, CRP, SJC). This implies a limit to the direct comparability of results obtained from subjective measures from different countries. Acknowledgments: Partly funded by grants from Nordforsk and Foreum Disclosure of Interests: Bénédicte Delcoigne: None declared, Sella Aarrestad Provan: None declared, Hilde Berner Hammer Consultant of: Has received fees as consultant from Roche, AbbVie and Novartis., Speakers bureau: Has received fees for speaking from AbbVie, BMS, Pfizer, UCB, Roche, MSD and Novartis, Daniela Di Giuseppe: None declared, Thomas Frisell: None declared, Bente Glintborg Grant/research support from: Grants from Pfizer, Biogen and Abbvie, Gerdur Gröndal: None declared, Björn Gudbjornsson Speakers bureau: Novartis and Amgen, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis, Brigitte Michelsen: None declared, Dan Nordström Consultant of: Abbvie, Celgene, Lilly, Novartis, Pfizer, Roche and UCB., Speakers bureau: Abbvie, Celgene, Lilly, Novartis, Pfizer, Roche and UCB., Heikki Relas Grant/research support from: Abbvie., Consultant of: Abbvie, Celgene, and Pfizer., Speakers bureau: Abbvie, Celgene, and Pfizer., Niels Steen Krogh: None declared, Johan Askling Grant/research support from: JA acts or has acted as PI for agreements between Karolinska Institutet and the following entities, mainly in the context of the ARTIS national safety monitoring programme of immunomodulators in rheumatology: Abbvie, BMS, Eli Lilly, Merck, MSD, Pfizer, Roche, Samsung Bioepis, Sanofi, and UCB Pharma